Gold-silver nanoparticles modified electrochemical sensor array for simultaneous determination of chromium(III) and chromium(VI) in wastewater samples. (October 2021) - Zhao, Ke; Ge, Liya; Wong, Ten It; Zhou, Xiaodong; Lisak, Grzegorz
Abstract: The oxidation state of ions is a crucial aspect that often has been overlooked when determining the toxicity of chromium (Cr) species in environmental samples. In this study, a novel electrochemical sensor array based on gold-silver nanoparticles modified electrodes was developed for simultaneous determination of the two main chromium species (Cr(III) and (VI)). Specifically, the working electrodes of screen-printed carbon electrodes (SPCEs) were modified with silver-gold bimetallic nanoparticles through electrochemical deposition for detection of Cr(VI). The silver-gold bimetallic nanoparticles were further oxidized to form stable silver-gold bimetallic oxide nanoparticles for the detection of Cr(III). The results showed that the addition of silver with a theoretical value of 1% of gold could contribute to the formation and stabilization of oxides on the surface of gold nanoparticles. After characterization, the two kinds of electrodes were integrated as an electrochemical sensor array for selective and sensitive detection of Cr(VI) and Cr(III). The linear range and limit of detection (LOD, identified by three times of signal-to-noise ratio) were found to be 0.05–5 ppm and 0.1 ppb for Cr(VI), and 0.05–1 ppm and 0.1 ppb for Cr(III), respectively. Finally, the electrochemical sensor array was proven for successful detection of Cr(VI) and Cr(III) in tap water, artificial saliva and artificial sweat samples, and monitoring of Cr(VI) and Cr(III) in chromium-containing wastewater treatment process. Combined with a handheld dual-channel electrochemical device, the simultaneous determination of Cr(VI), Cr(III) and total chromium contents can be easily achieved for various samples. Graphical abstract: Image 1 Highlights: Novel sensors modified with nano silver-gold and silver-gold oxides were developed. The sensors were successfully applied to detect Cr (III/VI) separately in real samples. Quantitative results of the sensors matched with spiked amount and HPLC-ICP/MS results.